Faktor Penentu Minat Wajib Pajak Atas Insentif Perpajakan UMKM di Masa Pandemi COVID-19 - Efa Rossana; Rida Perwita Sari (Ekonomis: Journal of Economics and Business, 2023)
This study aims to examine and obtain empirical evidence about the interest of taxpayers registered at KPP Pratama Sukomanunggal on tax incentives for DTP MSMEs during the COVID-19 pandemic. The variables that will be tested in this study are perceptions of social factors, perceptions of tax knowledge and financial conditions on taxpayers' interest. The method in this research is quantitative with hypothesis testing. The data in this study are primary data obtained by distributing questionnaires to 100 MSME taxpayers registered at KPP Pratama Sukamanunggal Surabaya. The analysis in this study uses the Partial Least Square (PLS) approach. The results showed that social factors did not affect the interest of MSME taxpayers to take advantage of tax incentives during the COVID-19 pandemic, while the perception of understanding of taxation and financial conditions had a positive effect on the interest of MSME taxpayers to take advantage of tax incentives during the COVID-19 pandemic.